5 CM FROM NOVEL TO FILM: ECRANIZATION STUDY AND STRUCTURE COMPARISON - Fitriyanti Bunga; alif affany; Karkono Supadi Putra (Multilingual, 2020)
This research aims to determine the ecranization process and the differences in plot, figures, and setting in the form of simplification, addition, or variation changes in the process of adaptation of the 5 CM novel by Donny Dhirgantoro to the film of the same title by director Rizal Mantovani. The method used in this study is descriptive with a qualitative approach. The research data source is the 5 CM novel and the 5 CM film. Data collection techniques are done by reading, watching, and capturing. The analysis guidelines for this research are researchers. The validity of the data used in this study was the validity of discourse. Reliability of data is obtained using the reliability of the test interraters. The results of the study of the 5 CM novel by Donny Dhirgantoro and the 5 CM film by Rizal Mantovani produced an ecranization process that is simplification, addition, and variation changes in the plot, figure, and setting.